Ultrafine-Grained Two-Phase High-Entropy Alloy Microstructures Obtained via Recrystallization: Mechanical Properties - Guillot, Ivan; Tyrman, Muriel; Perrière, Loic; Couzinié, Jean-Philippe P.; Lilensten, Lola; Prima, Frédéric; Dirras, Guy (Frontiers in Materials, 2020)
A metallurgical methodology has been set up to design alloys with improved mechanical properties such as strength-ductility synergy, via improved strain hardening. To this end, a multi-concepts approach including High-Entropy-Alloys (HEA), grain refinement, chemical contrast and using the transformation induced plasticity (TRIP) deformation mechanism has been implemented. The use of a conventional thermomechanical treatment comprising cold rolling followed by annealing at 650°C, produced two high entropy alloys with submicron alpha (hcp) and beta (bcc) phases. For Ti35-5-5 alloys, stress-induced martensitic transformation, and its subsequent reverse transformation during annealing at 650°C, led to a well-recrystallized state. A microstructure consisting of alpha and beta equiaxed grains was obtained, whose size increased within the submicron domain from about 300 nm to 600 nm with the holding time between 15 to 300 min. Contrariwise, for Ti35-6.5-6.5, which does not deform by the TRIP effect, the same thermomechanical treatment does not produce the recrystallization. Rather precipitation of platelets in the recovered beta matrix occurred. As for the mechanical properties, the yield strengths of the alloys with dual-phase microstructure lie between 950 and 1150 MPa for Ti35-5-5 and between 850 and 950 for Ti35-6.5-6.5 counterpart, for annealing times ranging from 15 min (higher yield strength) to 300 min (lower yield strength). This corresponds to a very large increase in the yield strength compared to that of the as-cast alloys, displaying values of about 400 MPa and 725 MPa for Ti35-5-5 and Ti35-6.5-6.5, respectively. Reasonable ductility was obtained for the alloys with optimized microstructures, that both display a tensile ductility of about 12% after annealing for 300 min at 650°C